A successful career in early childhood education: personal values of childcare trainees - Omar, Romarzila; Abdul Aziz, Nor Azah; Salleh Hudin, Norlaile; Che Mustafa, Mazlina; Md.Yassin, Sopia (International Journal of Evaluation and Research in Education (IJERE), 2022)
Early childhood education is a non-formal education for children under the age of six. The main aim of childcare centers is to prepare small children with basic knowledge before receiving a formal education as a first-grader in the primary schools. This paper discusses the findings of a study that focused on childcare trainees’ personal values in building a career in early childhood education. This study used the convergent parallel mixed method involving a survey and interviews, in which 1497 and 159 respondents were selected, respectively. Findings from qualitative data showed that childcare trainees had strong personal values by being respectful of their students, affectionate in taking care of children, and punctual in conducting their teaching lessons. Collectively, such traits can make these future teachers a good role model that students can emulate. More importantly, such strong personal values are extremely important to meet the strong demand for competent, caring childminders and early childhood education teachers, which has lately been made more urgent in view of the proliferation of childcare centers over the nation.